A Broken Public? Americans' Responses to the Great Recession. (October 2013) - Brooks, Clem; Manza, Jeff
Did Americans respond to the recent Great Recession by demanding that government provide policy solutions to rising income insecurity, an expectation of state-of-the-art theorizing on the dynamics of mass opinion? Or did the recession erode support for government activism, in line with alternative scholarship pointing to economic factors having the reverse effect? We find that public support for government social programs declined sharply between 2008 and 2010, yet both fixed-effects and repeated survey analyses suggest economic change had little impact on policy-attitude formation. What accounts for these surprising developments? We consider alternative microfoundations emphasizing the importance of prior beliefs and biases to the formation of policy attitudes. Analyzing the General Social Surveys panel, our results suggest political partisanship has been central. Gallup and Evaluations of Government and Society surveys provide further evidence against the potentially confounding scenario of government overreach, in which federal programs adopted during the recession and the Obama presidency propelled voters away from government. We note implications for theoretical models of opinion formation, as well as directions for partisanship scholarship and interdisciplinary research on the Great Recession.